Innovative post mastectomy bra for increasing self-convenience and confidence patients - Susilawati, Oting; Santosa, Agus (MEDISAINS, 2019)
Background: The act of mastectomy can affect body image because it loses part of the body and affects their social relationships with others. The existed bra is felt uncomfortable when worn so it is necessary to develop a special post mastectomy bra to increase the confidence and comfort of post mastectomy patients.Purpose: This study aimed to examine and develop a special post mastectomy bra to increase self-confidence in post-mastectomy patients.Research Methods: This is a Research and Development (R & D) research. This study consisted of 3 phase, namely research phase I, phase II, and phase III or product testing.Results: The results of a post mastectomy special bra tested to 10 respondents mentioned that a special post mastectomy bra is comfortable to wear and they are not ashamed anymore do activities outside the home.Conclusion: Special post mastectomy bras are proven to increase post-mastectomy patients' convenience and confidence.